Experience, Authority, and Social Critique: A Comparison of Margaret Farley and John Dewey - Dunn, Shannon (Feminist theology, 2016)
The category of experience has constituted an important point for reflection in moral philosophy and theology, particularly among feminist and liberationist circles. The appeal to experience as an authoritative source has been met with criticism by those who understand the term to connote either radical interiority, on the one hand, or an uncritical foundation for truth claims, on the other. This essay argues that the respective works of classical pragmatist, John Dewey, and Catholic feminist theologian, Margaret Farley, provide a compelling alternative to these characterizations of experience, which can help scholars in ethics and theology to better articulate the relationship of individual and social experience, as well as the ways by which people use experience to give legitimacy to moral practices.